NMDA receptor partial agonist GLYX-13 alleviates chronic stress-induced depression-like behavior through enhancement of AMPA receptor function in the periaqueductal gray. (1st November 2020) - Yang, Po-Sheng; Peng, Hsien-Yu; Lin, Tzer-Bin; Hsieh, Ming-Chun; Lai, Cheng-Yuan; Lee, An-Sheng; Wang, Hsueh-Hsiao; Ho, Yu-Cheng
Abstract: Depression is a common mental disorder affecting more than 300 million people worldwide and is one of the leading causes of disability among all medical illnesses. The accumulation of preclinical data has fueled the revival of interest in targeting glutamatergic neurotransmission for the treatment of major depressive disorder. GLYX-13, a glutamatergic compound that acts as an N -methyl-d -aspartate (NMDA) modulator with glycine-site partial agonist properties, produces rapid and long-lasting antidepressant effects in both animal models and patients. However, the mechanisms underlying the antidepressant actions of GLYX-13 have not been fully characterized, especially in the midbrain ventrolateral periaqueductal gray (vlPAG), a brain stem area that controls stress-associated depression-like behavior. Here, we use a combination of electrophysiological recordings, behavioral tests, and pharmacological manipulations to study the antidepressant actions of GLYX-13 in the vlPAG. A single intravenous injection of a GLYX-13 rapidly mitigated footshock stress (FS)-induced depression-like behavior in rats. The FS-induced diminished glutamatergic transmission in the vlPAG was also reversed by a single GLYX-13 intravenous injection. Moreover, intra-vlPAG GLYX-13 microinjection produced a long-lasting antidepressant effect; however, this effect was prevented by the intra-vlPAG microinjection of tropomyosin-related kinase B (TrkB) receptor antagonist ANA-12, a selective mammalian target of rapamycin complex 1 (mTORC1) inhibitor rapamycin, and CNQX, an AMPA receptor antagonist. Additionally, a bath application of GLYX-13 enhanced glutamatergic transmission in vlPAG neurons; however, this enhancement effect was blocked by the co-application of ANA-12 and rapamycin. These results demonstrate that BDNF-TrkB-mTORC1 signaling in the vlPAG is required for the sustained antidepressant effects of GLYX-13. Highlights: Intravenous injection of GLYX-13 alleviates stress-induced depression-like behavior. Intra-vlPAG microinjection of GLYX-13 rescues stress-induced depression-like behavior. GLYX-13 ameliorates stress-induced depression-like behavior through BDNF-TrkB-mTORC1 signaling.